Le joueur en crise(s) : instant et répétition, néant et éternité - Natalia Leclerc (Temporalités)
When confronted with the roulette, the gambler goes through a moment of crisis. Actually, he goes through two different types of crises: the one that leads him to compulsive gambling and represents the unique and founding crisis of his existence; the other, of a repetitive nature, is the one he goes through every time the roulette turns. In both cases, the crisis, which is dialectical in nature, is characterised by its temporal nature – instantaneity. Dostoyevsky, in The Gambler, and Zweig, in Twenty-Four Hours in the Life of a Woman, stage these crises through a set of characters who represent their different aspects. Furthermore, we can find parallels between both novels, as Zweig’s novel echoes Dostoyevsky’s work, whom he reads and comments upon.Gambling is never simply a form of entertainment. It is always presented as a form of ordeal: the subject’s entire existence is invested in the decisive moment. Nonetheless, the gamble does not necessarily end with death. The greatest risk that the gambler runs is that of coming upon the void that results from an eternity of repetition. For the compulsive gambler, the crisis, of a tragic nature, cannot lead to a positive outcome and is linked to the absence of freedom and to a mechanical and/or animal form of temporality.